Exoscopic Minimally Invasive Excision of Intradural Extramedullary Tumor - Debabrata Sahana; Lavlesh Rathore; Sanjeev Kumar; Rajiv K. Sahu (Indian Journal of Neurosurgery)
Spinal tumors extending up to two levels can be removed using minimally invasive techniques. A microscope is traditionally used as a visualization tool with the tubular-retractor system. An exoscope is a newer optical tool with improved digital resolution, panoramic view, and better ergonomics for surgery. A 36-year-old who presented with paraparesis was diagnosed with intradural extramedullary tumor in the T7-T8 region. A complete tumor resection was possible using tubular retractors and exoscope. The patient recovered clinically. We document our surgical experience and present an edited video of the surgery. The key steps and nuances are described in the audio timeline. The authors acknowledge the feasibility of performing this surgery via a minimally invasive method using an exoscope.